Economia circular no segmento de embalagens - Paixão, Fernando Pimentel (2023)
The packaging sector serves as an important indicator of growth or decline in industrial production, due to its wide variety of uses in the market. Packaging has a direct participation in the quantification of costs and manufacturing technology, being considered an inseparable part of the value chain of the final product to be delivered. Innovation made possible through the circular economy appears as a valid alternative in any type of scenario, helping to reduce the amount of material used in packaging and the waste it generates. This bibliographic review research was divided into stages. First, an analysis of successful cases of innovative solutions arising from the three sectors with the highest representation in the Upstream Innovation guide was carried out. Then, from the comparison of the analyzes with the information obtained from the literature, a brief world overview of the circular economy was elaborated. And, finally, according to what was researched, a study was carried out of elements that appear as opportunities that stimulate innovation in packaging in Brazilian companies through the application of the circular economy. In the end, it was concluded that there is a direction from large industries, brands and retailers to enable the transition from a linear model to a circular model, with a migration to the reuse of materials to the detriment of disposal, which consequently allows a more efficient production. clean and conscious.